Flipping the hidden curriculum to transform pain education and culture - Mardian, Aram S.; Villarroel, Lisa; Quist, Heidi E.; Chang, Lynn E.; Mintert, Jeffrey S.; Su, Tiffany N.; Dhanjal-Reddy, Amrita; Hanson, Eric R. (Frontiers in Pain Research, 2023)
Though long-sought, transformation of pain management practice and culture has yet to be realized. We propose both a likely cause—entrenchment in a biomedical model of care that is observed and then replicated by trainees—and a solution: deliberately leveraging the hidden curriculum to instead implement a sociopsychobiological (SPB) model of care. We make use of Implicit Bias Recognition and Management, a tool that helps teams to first recognize and “surface” whatever is implicit and to subsequently intervene to change whatever is found to be lacking. We describe how a practice might use iterations of recognition and intervention to move from a biomedical to a SPB model by providing examples from the Chronic Pain Wellness Center in the Phoenix Veterans Affairs Health Care System. As pain management practitioners and educators collectively leverage the hidden curriculum to provide care in the SPB model, we will not only positively transform our individual practices but also pain management as a whole.